Integrated anatomical practice combining cadaver dissection and matched cadaver CT data processing and analysis. - Kawashima, Tomokazu; Sakai, Makoto; Hiramatsu, Keita; Sato, Fumi (Surgical & Radiologic Anatomy, 2022)
Purpose: With the increasing significance of diagnostic imaging in clinical practice, long-term anatomical education and training is required to ensure that students can reliably distinguish anatomical structures and interpret images. To improve students' motivation and prospects for learning imaging anatomy, we developed an integrated anatomical practice program combining cadaveric dissection with cadaver CT data processing and analysis during undergraduate students' dissection courses. Methods: Workstations imported with post-mortem CT data of dissected cadavers and various forms of clinical CT/MRI data were set in the dissection room. Medical students had free access to the imaging data during cadaver dissection, and they were challenged to process and analyze the data for submission of voluntary imaging reports on their topics of interest. Finally, we surveyed the integrated anatomical education of 481 medical students. Results: The positive response rate to the integrated anatomical practice was 74.9%, and 79.4% of the students answered that this form of practice offered a suitable introduction to anatomical imaging. The usefulness of this approach in understanding the 2- to 3D arrangement of the human body and enhancing interest in anatomy was also confirmed. The submission rate of voluntary imaging reports also increased annually and is currently 97.4%. Conclusion: Our integrated anatomical practice only allowed students to actively browse CT images and facilitated imaging processing and analysis of their region of interest. This practice may improve students' long-term ability to analyze images and deepen their understanding. A competitive imaging contest may help improve students' motivation when they begin learning imaging anatomy.